Callogobius liolepis Bleeker, a senior synonym of Gobiopsis aporia Lachner and McKinney (Teleostei: Gobiidae: Gobiopsis) - Delventhal, Naomi R.; Mooi, Randall D. (Zootaxa, 2013)
Callogobius liolepis Bleeker in Koumans was briefly described from two specimens from Ambon. A later, more detailed description by Koumans was apparently based on Bleeker’s unpublished description and specimens of C. okinawae (Snyder), considerably complicating the taxonomy of several species. Re-examination of the syntypes identifies C. liolepis as a species of the genus Gobiopsis Steindachner due to the absence of raised vertical ridges of papillae that characterise Callogobius and the presence of barbels in a pattern unique among gobiids to a subset of Gobiopsis. Gobiopsis liolepis (Bleeker) is determined as the senior synonym of G. aporia Lachner and McKinney based on the absence of head pores combined with the presence of a series of tightly spaced papillae over the eye, lateral scale counts of 36–42, pectoral-fin ray counts of 20–21, dorsal-fin ray counts VI+I,10 and anal-fin ray counts of I,9. The larger syntype is designated the lectotype and the smaller the paralectotype. Specimens identified as C. liolepis in museums or the literature are likely referable to C. okinawae (Snyder) or C. bifasciatus (Smith).